Therapeutic advances in overcoming intrauterine growth restriction induced metabolic syndrome - Mutamba, Alpha Kalonda; He, Xiaori; Wang, Tao (Frontiers in Pediatrics, 2023)
Intrauterine growth restriction (IUGR) greatly impacts an organism’s normal biological development and internal metabolism. We are directing our focus for this review on providing an overview of the impact of IUGR on the internal metabolism along with different biological parameters that are affected. We do also point out some relevant therapies under investigation. We first elaborate on the characteristics and causes of IUGR by pointing out recent findings, then organs that are greatly affected, followed by animal models commonly used in various studies, and the impact of IUGR on global health and the economy. Secondly, we discuss various metabolic disorders and metabolic imbalances with their genetic implications resulting from IUGR, such as insulin resistance, type 2 diabetes mellitus, lipid metabolism, obesity and the hepatic redox status. At last, we summarize some prospective therapies used in different studies.